Rancang Bangun Alat Viskositas Zat Cair Menggunakan Sensor Inframerah Sebagai Detektor Waktu Pada Praktikum Viskositas Zat Cair Matakuliah Fisika Dasar - Agus Wahid Habiburrohman; Fauzi Fauzi (Prodi Fisika FKIP Unram, 2020)
Abstract—Physics practicum is needed in understanding the concept of learning, one of which is the law to determine the viscosity value of a liquid. One method that is often used in determining the viscosity coefficient is the falling ball method, however, there is a weakness in this method, namely the drop time is very fast so it is difficult to get the exact and accurate time so that the calculation of the viscosity coefficient value is not accurate. Therefore a detection device is needed so that it can get a more precise and accurate time value. This study aims to determine the viscosity coefficient of cooking oil at room temperature with an infrared sensor as a time detector so that it is expected to obtain a precise and accurate time and to produce a more accurate calculation of the viscosity coefficient. The purpose of this research is to make a viscosity tool that has good data accuracy and can be used in physics practicum.